Strategi Pelayanan Pelatihan Kontrasepsi Pada Program Keluarga Berencana di Badan Kependudukan dan Keluarga Berencana Nasional Provinsi Jawa Timur - Khofifah, Nor; Meirinawati, Meirinawati (Publika, 2024)
Contraceptive services are one of the efforts in the Family Planning (KB) program. The family planning program was formulated to overcome several population problems in Indonesia, including the still high maternal and infant mortality rates, decreased use of contraception, low public understanding of reproductive health and the need for family planning which has not been properly served. BKKBN East Java Province through the 2020-2024 Strategic Plan (Renstra) provides contraceptive training services. This research aims to analyze the East Java Province BKKBN in contraceptive training services for midwives. Researchers used descriptive qualitative research methods with data collection methods through observation, interviews, documentation and literature study. The focus of this research uses the theory of training program strategy stages according to Widiastri (2019) which consists of four (4) indicators, namely the program planning process, training program process, evaluation and monitoring. The results of the research explain that the strategy used by the East Java Province BKKBN, seen from the indicators of the program planning process, has been carefully prepared through preparatory meetings, in the indicators the East Java Province BKKBN training program process is running smoothly and structured, then the evaluation indicators are that there are several obstacles during contraceptive training namely that there are still midwives who are less skilled when practicing services, the website used is less than optimal and the East Java Province BKKBN monitoring indicators can provide insight regarding the importance of contraceptive use. The suggestions that researchers give in this study are 1) BKKBN East Java Province to be more aggressive in disseminating information about Family Planning, 2) make assessment sheets transparently and 3) be able to develop learning media used during contraceptive training.